Screening of carbamazepine-saccharin (CBC-SAC) co-crystal - Nur Amanina, Mohamad Adaris (2017)
Co-crystallization is a method in formulation of drug products which is believed to improve drugs solubility, stability and dissolution rate while maintaining the biological functions of its chemical properties. The recent advances in this area have brought this research possible in order to produce pharmaceutical material by crystallization design of carbamazepine (CBZ) using saccharin (SAC) as its co-crystal. This research is conducted to examine formation of carbamazepine-saccharin (CBZ-SAC) co-crystal screening approaches that uses different solvent based crystallization technique in varies solvent system (ethyl acetate solvent and formic acid solvent). In this method, to prepare the co-crystal product CBZ-SAC four crystallization technique are used which are cooling crystallization, solvent crystallization, slurry and stirring in varies solvent of ethyl acetate and formic acid. Different mol ratio of CBZ and SAC are being tested, in order to study CBZ-SAC co-crystal formation. Physical characterization of the co-crystal is being characterized by x-ray powder diffraction (XPRD), differential scanning calorimetry (DSC), fourier transform infrared spectroscopic (FTIR) and optical microscopic. The XPRD analysis had confirmed that only CBZ-SAC co-crystal in ethyl acetate solvent were successfully formed while in formic acid solvent the crystal formed were only SAC. The XRPD pattern profile analysis shown that CBZ-SAC Form I and Form II was produced from different ratios and different methods and it have their own melting point based from the DSC analysis which are 170-172°C and173-177°C respectively. The morphology of the crystal are mostly plate like and needle like shape which indicate Form I and Form II respectively for the polymorphic characterisation. Since two type of polymorph were successfully produced, it is shown that solvent, methods and ratios plays an important role to CBZ-SAC co-crystal formation. Further study in screening is needed for co-crystal formation assessment since there were already many factors proven in affecting the polymorphic formation of the co-crystal such as different methods, solvent and mole ratio. Besides that varies solvent type should be implemented to investigate if the solvent yield CBZ-SAC co-crystal formation and its polymorph.